THE PATTERNS OF CHANGE IN LENGTH OF THE CORONARY ARTERIES IN HUMANS IN THE SECOND PERIOD OF MATURE AGEAND IN EARLY OLD AGE - T. S. Zharikova; V. E. Milyukov; V. N. Nikolenko (Сеченовский вестник, 2018)
The aim of this work is to identify the individual characteristics of the coronary arterial bed (length of channels of the coronary arteries and values of the total lengths of their channels) in different age groups in men and women in norm.Materials and methods. We investigated coronaroangiogramms of 107 people, aged 36 to 74 years. All of the examined coronary angiography was performed in State budgetary institution “A.N. Bakulev Scientiﬁc center of cardiovascular surgery” (Director - doctor of medical Sciences, Professor, academician L.A. Bockeria) in 2012, according to the results of examination of pathological changes of coronary arteries was revealed. Among the surveyed women was 50 (46.7 %) and 57 men (53.3 %). Morphometry was carried out in one projection (left anterior oblique to both of the coronary arteries) using the software Syngo Fast View, Adobe Photoshop CS7, statistical data processing - using Microsoft Excel, SPSS.Results. In the elderly people as average and median values of the total length of the branches of the channel of right coronary artery (i. e., all rendered angiography its branches) and the total length of the coronary vessels are greater than the same in people of the second period of mature age.